Research on Simulation System for Human-SRL Collaborative Motion Planning - Xiaobo Zhang; Jinguo Liu; Yangmin Li (Journal of Robotics)
At present, there is a problem of visual area switching in the existing SRL (supernumerary robotic limb) operation methods. In response to this problem, the authors’ previous work proposed a new SRL operation method called relatively independent operation, and proposed a corresponding software architecture. The purpose of this paper is to solve the theoretical problems and engineering realization problems of the human-SRL skeleton algorithm module in the software architecture. Therefore, modeling, data collection, data processing, and visualization of a human-SRL system are studied in this paper. Firstly, a human-SRL skeleton visualization simulation system is developed. The condition setting, the applications, and the core algorithm of the simulation system are introduced. The core algorithm mainly contains four types of important functions, namely skeleton model building functions, human-SRL data collection functions, human-SRL data processing functions, and skeleton visualization functions. Secondly, the implementation principles of these four functions are described: (1) For the skeleton model building functions, a human-SRL skeleton model is proposed which is an integration of a human skeleton model and an SRL skeleton model. The construction methods of these three skeleton models are described. (2) For the remaining functions, how to collect and process human data, SRL data, human-SRL data, and how to visualize a human-SRL skeleton are described. Finally, the visualization effect of the developed simulation system on human-SRL skeleton movement is verified by experiments, which proves the correctness of the functions in the simulation system.